2020
DOI: 10.3390/ani10071213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Milking Units on the Pulsation Curve in Dairy Sheep Milking

Abstract: Mechanical milking is a critical operation in ewe dairy farming where the operative parameters and the milking routine strongly influence milk production and animal welfare. The challenge in adapting dairy animals to the farm environmental conditions may cause illness and compromise the quality of the products. From this perspective, it is important to evaluate the technological and operational aspects that can influence milk quality and animal welfare. Thus, the aim of this work was to investigate the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The most important equipment in a dairy farm environment is the milking parlour. Teatcups in a milking parlour can contribute to the dissemination of bacteria into the mammary gland [ 1 , 2 ]. Indeed, Liagka et al [ 3 ] have recently indicated that bacteria on teatcups can enter into the teat of ewes during the milking routine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important equipment in a dairy farm environment is the milking parlour. Teatcups in a milking parlour can contribute to the dissemination of bacteria into the mammary gland [ 1 , 2 ]. Indeed, Liagka et al [ 3 ] have recently indicated that bacteria on teatcups can enter into the teat of ewes during the milking routine.…”
Section: Introductionmentioning
confidence: 99%
“…All these can be exacerbated during a malfunction or improper use of the milking machine, as it may affect teat status, causing changes or even lesions, which would facilitate the onset of mammary infection [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%